La privatisation des espaces publics en milieu urbain : le cas de Montréal. - Momer, Bernard P. (University of Ottawa (Canada), 1991)
The public place has always provided a space where the social, commercial and political functions, generated by the sedentary way of life, were held. Although its functions have not greatly changed through time, the form of the public place has evolved to become an interior space. The fast growing development of the large cities in the last thirty years, has encouraged the construction of multipurpose complexes and shopping centres, which have taken over the role of the public place. This shift of the functions of the public place towards the interior is also a shift of the public space towards a privatized space, since most multipurpose complexes and shopping malls are privately owned. The study of this phenomenon, commonly known as the privatisation of public space, brings us to reflections on the freedom of the population and on the current and future planning of our cities.
Keywords: Geography.